Mycogenic silver nanoparticles from Penicillium citrinum IB-CLP11 - their antimicrobial activity and potential toxicity effects on freshwater organisms - Aguiar, Arthur Pérez [UNESP]; Ottoni, Cristiane Angélica [UNESP]; Aquaroli, Claudia de Lima Ramos [UNESP]; Mendes, Evelyn Caroline Vicente [UNESP]; Araújo, Ana Lúzia de Souza; Simões, Marta Filipa; Barbieri, Edison (Royal Society of Chemistry (RSC), 2024)
Silver nanoparticles (AgNPs) are some of the most attractive nanomaterials for commercial applications, but they can also be a very challenging issue from the point of view of cytotoxicity and phytotoxicity as agents that damage genetic information within a cell, causing mutations. AgNPs can be easily biosynthesized mainly by fungi which release enzymes in response to stress conditions, reducing silver ions to nanoscale size. Nowadays, mycogenic AgNPs are becoming increasingly relevant for several industrial and environmental applications; therefore, we urgently need to understand in detail how these AgNPs act and their potential effects on the environment to take measures to prevent the occurrence of hazards. The present work had the goal of evaluating the effect of spherical AgNPs synthesized by Penicillium citrinum IBCLP11 (AgNPsIBCLP11), with an average diameter of 57.5 ± 4 nm, against the pathogenic bacteria Pseudomonas aeruginosa IPT322, Staphylococcus aureus IPT246 and Klebsiella pneumoniae IPT412 and their potential toxicity to the freshwater organisms Chlorella vulgaris, Palaemon pandaliformis and Danio rerio. AgNPsIBCLP11 presented the minimum inhibitory concentration of 15 μg mL−1 for the IPT322 strain, while for IPT246 and IPT412, it ranged from 20 to 25 μg mL−1. For all freshwater organisms studied, the AgNP toxicity was lower than that of their metal precursor. C. vulgaris growth and survival rates after 72 h of exposure to AgNPsIBCLP11 were not affected at concentrations ranging from 10 to 100 μg L−1. AgNPsIBCLP11 and silver nitrate (AgNO3) caused no acute toxicity on adult zebrafish, although they did induce several physiological changes. In view of the results obtained, the AgNPs showed promising potential for their use in freshwater system decontamination, especially against pathogenic microorganisms, making it possible to reduce deleterious impacts on the ecosystem and enabling the conservation and management of this natural resource.